TREATMENT OF PALM OIL MILL EFFLUENT (POME) USING MORINGA OLEIFERA SEEDS AS NATURAL COAGULANT AND NANOFILTRATION MEMBRANE - Naidu GenggayaNaidu, Thineswary (IRC, 2017)
Palm oil mill effluent (POME) is waste effluent from the production of palm oil and considered hazardous to the environment because it has a high biochemical oxygen demand (BOD), chemical oxygen demand (COD), total suspended solids(TSS), oil and grease, turbidity and acidic in nature. This project discusses and reports on the development of Moringa Oleifera seeds as a natural based coagulant, its efficiency in the POME pre-treatment process and nanofiltration membrane technology to treat POME. The pre-treatment is carried out by performing a jar test to obtain the optimum coagulant dosage followed by nanofiltration membrane separation. The nanofiltration membrane separation was carry out in a stainless steel Sterlitech stirred cell from United States. Based on the study conducted, it can be concluded that there is a significant reduction in the BOD, COD, pH, TSS and turbidity of the POME. The raw POME has a characteristic of 2,410 mg/L, 3,900 mg/L, 865 NTU, 41,900 mg/L for BOD, COD, turbidity and TSS, respectively. Meanwhile the pH is about 4.61. After undergoing the pre-treatment and membrane separation process, the reduction in the parameters are 91.7%, 83.0%, 67.7% and 72.8% for BOD, COD, TSS and turbidity, respectively. Meanwhile the pH has increased to 4.88.